Biomechanical analysis of distraction forces on the posterior meniscal roots to optimize early rehabilitation protocols. Issue 9 (28th September 2020) - Ellermann, Sophia; Kittl, Christoph; Frank, Andre; Wermers, Jens; Glasbrenner, Johannes; Briese, Thorben; Raschke, Michael J.; Herbort, Mirco; Herbst, Elmar
Introduction: The aim of this study was to investigate the distraction forces of the medial and lateral posterior meniscal roots after repair (PMMR, PLMR) at different degrees of flexion and axial load. Hypotheses: It was hypothesized that with increasing axial load and flexion angle, the distraction forces on the meniscal roots increase continuously. Methods: Eight fresh-frozen human cadaveric knees were axially loaded in a custom made kinematics rigs with 0 N, 200 N and 400 N throughout a continuous flexion-extension cycle (0°-90°). The distraction forces acting on the PMMR and PLMR were determined in three scenarios: 1) native knee joint, 2) after bilateral detachment of the posterior meniscal roots and following root repair, 3) after resection of the anterior cruciate ligament (ACL). To measure the distraction forces, the FiberWire No. 2 (Arthrex, Inc.) sutures used for the root repairs were shuttled transtibially through a 2.4 mm bone tunnel and tied over a force sensor mounted on the anterior tibia with a pretension of 2 N. Statistical analysis was performed using a repeated- measures ANOVA with a post-hoc Bonferroni correction (p < 0.05). Results: Overall, the different investigated knee states as well as the degree of flexion showed a significant effect on the distraction forces on the posterior meniscal roots (p <0.01). An axial load of 200 N and 400 N resulted in a significant increase of the distraction forces on both menisci over the entire range of motion compared to an unloaded state (p < 0.01). When no axial load was applied, the distraction forces after PMMR and PLMR refixation were not significantly affected by the degree of flexion (p > 0.05). With axial loading of 200 N and 400 N, the distraction forces on the PLMR were significantly higher at flexion angles between 15° and 90° compared to full extension (p <0.01). In contrast, the distraction forces on the PMMR were highest close to extension (0° -30°) and decreased significantly towards 90° of flexion when the knees were loaded with 200 N and 400 N (p <0.01). When the ACL was removed, a significant increase of the distraction forces at the posterior meniscal roots was observed (p < 0.001). Conclusion: Axial loading significantly increases the distraction forces after posterior meniscal root repair. Therefore, axial loading should be avoided in the early postoperative phase. Furthermore, data of this study shows that passive exercise between 0° and 90° flexion can be performed without significantly affecting the forces acting on the menisci.